Obolevnost prebivalcev Slovenije za akutnim koronarnim sindromom v povezavi z nekaterimi meteorološkimi spremenljivkami - Ravljen, Mirjam (visokošolska dela, 2016)
Acute Coronary Syndrome (ACS) is as a result of a sudden reduction of blood flow to part of the heart caused by a blood clot. It represents the main cause of dying of approximately 1.8 million people in Europe. Many researches associate the appearance of diseases with the weather. In Slovenia the problem has not been studied yet. The correlation between an average daily temperature, humidity and barometric pressure as well as the incidence of ACS, within the period of 1st January 2008 until 31st January 2011 was analyzed by means of Poisson regression analysis. The results have shown the incidence of all treated patients to be negatively correlated with average daytime temperature on the same day as well as all week before, humidity up to two days as well as 5 to 7 days and air pressure up to four days before. In patients, older than 65 years it turned out that, only temperature is negatively correlated with the occurrence of diseases. These findings are comparable to research results from most European countries. The incidence of the disease in patients, younger than 65 years, is negatively correlated with humidity and barometric pressure. The number of researches that have analyzed these impact is low, the results are contradictory and pathophysiological mechanism remains unclear.
Keywords: Akutni koronarni sindrom; Incidenca; Slovenia; Slovenija; Disertacije; bioklimatologija; cardiovascular disease; kardiovaskularne bolezni; obolevnost; dejavniki tveganja; vreme; weather; vremenske spremenljivke; temperatura; vlažnost; Humidity; zračni tlak